Determinasi Financial Distress Industri Otomotif Jerman: Rasio Keuangan dan Faktor Makroekonomi - Rahel Sintya Febrianti Simbolon; Fitria Husnatarina; Verra Rizki Amelia; Iwan Christian (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the effect of financial ratios and firm size on financial distress conditions in the German automotive industry during the period 2019–2024, while considering macroeconomic pressures represented by the energy price index and inflation. The background of this study is driven by increasing external pressures resulting from the Russia–Ukraine war, which has led to rising energy costs, supply chain disruptions, and global economic instability. This research employs a quantitative approach using secondary data obtained from the annual reports of automotive companies listed in the DAX index. The sampling technique applied is purposive sampling, resulting in 7 companies with a total of 42 observations. The analytical method used is panel data regression with the assistance of EViews 12 software, including the estimation of the Common Effect Model, Fixed Effect Model, and Random Effect Model, along with classical assumption tests and both partial and simultaneous hypothesis testing. The results show that, partially, liquidity ratio, solvability ratio, and firm size do not have a significant effect on financial distress, whereas profitability ratio has a significant effect. However, simultaneously, all variables—including macroeconomic variables—have a significant influence on financial distress. The Adjusted R² value of 0.930369 indicates that the model is able to explain 93.04% of the variation in financial distress conditions. These findings highlight that profitability is a key indicator in predicting financial distress and emphasize the importance of integrating both internal and external factors in understanding corporate financial risk amid geopolitical and global economic dynamics.